WASTEWATER TREATMENT OF PIGMENT PRODUCTION PLANTS IN TWO STAGES: PREPARED ACTIVATED CARBON AND ELECTRODIALYSIS PROCESS - Mohammed Q. Gubari; Bilal S. Taha (Ползуновский вестник)
One of the most important factors limiting the development of industrial processes is the consumption of large amounts of clean water and the generation of large amounts of wastewater. Pigments are available in a wide range of colors, consisting of small molecules practically insoluble in the medium and known to be unique compounds for many industries. They are widely used in dyestuff, cosmetics, food products, pharmaceuticals, manufacturing processes, etc. This study focuses on the removal of pigments and other components from wastewater discharged from pigment plants. The separation process was carried out in two stages: the first was to use prepared activated carbon as an adsorbent to separate the pigment, and then the separation process by electrodialysis to remove other components such as salts, acids, and others. This study considers prepared activated carbon (AC) as an effective separating adsorbent. The preparation process mainly included two-stage pyrolysis and activation using potassium hydroxide (KOH) and sodium hydroxide (NaOH).